DEVELOPING ENGLISH INTERACTIVE LEARNING MEDIA BASED ON ANDROID BY USING ARTICULATE STORYLINE 3 APPS - Uzmi, Almira Humaira (ELP (Journal of English Language Pedagogy), 2023)
This study was conducted in response to the challenges encountered by students in learning English within an academic context. The identified issues included a lack of interactive learning resources, difficulties in comprehending English materials, limited opportunities for practice, and time constraints within the classroom. Consequently, the aim of this research was to develop an Android-based English interactive learning app using the Articulate Storyline 3 application, specifically tailored to support students in an academic setting.The research employed the Research and Development (R&D) methodology, utilizing the 4-D (four-D) version and following the Luther-Sutopo model for system development. The target population consisted of seventh-grade students at SMPIT Al-Fityah Pekanbaru, with a sample size of thirty students. Data were collected through questionnaires and a pretest-posttest procedure. Statistical analysis involved the utilization of Aiken's V formula, the Moment Kappa formula, and the t-test formula. The study yielded three key results. Firstly, the validity test demonstrated a high validity score of 0.88, indicating the reliability and appropriateness of the developed learning app for its intended academic purposes. Secondly, the practicality test produced a score of 0.98, indicating that the learning app was practical and feasible to be used within the academic teaching and learning process. Lastly, the effectiveness test revealed a significant improvement, with a two-tailed significance score of 0.00, which was smaller than the significance level of 0.005. This indicates that the learning app was highly effective in facilitating the academic teaching and learning process. Based on the results of the three tests, it can be concluded that the developed app provides a valuable tool for both teachers and students in the academic English learning process.